Variability of the characteristics of a migraine attack within patients. (August 2016) - Viana, M; Sances, G; Ghiotto, N; Guaschino, E; Allena, M; Nappi, G; Goadsby, PJ; Tassorelli, C
Background: Migraine attacks may present different features in different patients and also within the same patient. The percentage of patients reporting stereotyped attacks and those reporting attacks with different phenotypes has not been the object of specific investigations. Objective: The objective of this article is to evaluate the percentage of migraine patients reporting the same characteristics, in terms of phenotype and response to symptomatic medications on three consecutive migraine attacks. Methods: Thirty patients with migraine without aura prospectively recorded the features of three consecutive attacks in a headache diary. Characteristics recorded were: pain intensity, presence of nausea, vomiting, photophobia, phonophophia, osmophobia, allodynia, cranial autonomic symptoms (at least one), and premonitory symptoms. Patients were allowed to take frovatriptan as symptomatic medication, whose efficacy was evaluated as the two hours pain-free status. Results: None of the patients presented identical characteristics on the three studied attacks. This was still the case if we reduced the number of variables evaluated from 11 to seven of the eight core features indicated by the ICHD. Considering just six variables: unilaterality and quality of pain, presence/absence of nausea, vomiting, photophobia and phonophobia, only two patients (6%) had identical features on three consecutive attacks. With respect to the response to frovatriptan, 39% of patients had the same response, either positive (i.e. pain free after two hours) or negative (i.e. not pain free after two hours) on three consecutive attacks. Conclusion: Migraine attacks show a high variability not just among patients, but also within the same patient. Our data indicate that stereotypy of attacks is uncommon, and reinforces the underlying logic of the current operational classification system.